2003
DOI: 10.2136/sssaj2003.1243
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Conductivity in a Piñon-Juniper Woodland

Abstract: shrublands (Elkins et al., 1986;Lyford and Qashu, 1969;Wainwright et al., 2000), mesquite rangelands (Wood In semiarid environments, vegetation affects surface runoff either and Blackburn, 1981), and piñ on-juniper rangelands in by altering surface characteristics (e.g., surface roughness, litter absorption) or subsurface characteristics (e.g., hydraulic conductivity).the USA (Roundy et al., 1978). Similar findings have Previous observations of runoff within a piñ on-juniper [Pinus edulis been reported from ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 42 publications
9
90
3
Order By: Relevance
“…Disturbance events such as wildfire not only affect evapotranspiration but also reduce the rate of infiltration into the soil, leading to enhanced streamflow in regions with a Mediterranean or semi-arid climate (Hallema et al 2017). The streamflow regulation functions of forests depend on many watershed factors including background climate, forest structure (i.e., species composition, ages), soil properties such as hydraulic conductivity (Wilcox et al 2003b), geology, and watershed size ). It appears that the hydrological regulation functions of forests are scaledependent, and most of our knowledge is derived from small watershed vegetation manipulation experiments, and we lack empirical data about the role of vegetation in influencing streamflow of large river systems.…”
Section: Water Cycle and Supplymentioning
confidence: 99%
“…Disturbance events such as wildfire not only affect evapotranspiration but also reduce the rate of infiltration into the soil, leading to enhanced streamflow in regions with a Mediterranean or semi-arid climate (Hallema et al 2017). The streamflow regulation functions of forests depend on many watershed factors including background climate, forest structure (i.e., species composition, ages), soil properties such as hydraulic conductivity (Wilcox et al 2003b), geology, and watershed size ). It appears that the hydrological regulation functions of forests are scaledependent, and most of our knowledge is derived from small watershed vegetation manipulation experiments, and we lack empirical data about the role of vegetation in influencing streamflow of large river systems.…”
Section: Water Cycle and Supplymentioning
confidence: 99%
“…Studies have found higher infiltrability for subcanopy soils due to many factors including the protection of the soil surface by leaf litter, enhanced aggregation of soil particles, and more developed macropore networks (Dunkerley, 2000;Wilcox et al, 2003). Owing to these effects, the magnitude of infiltration and soil moisture has been shown to be higher under vegetation than intercanopy areas under certain conditions (Bhark and Small, 2003).…”
mentioning
confidence: 99%
“…At the Los Piños sites, due to the similarities between grama grass and juniper n-alkane signatures, there was a degree of difficulty in determining between sources; based upon n-alkane signature, a problem was previously experienced when using n-alkane signatures alone [Marschner et al, 2008;Gocke et al, 2011]. However, the use of n-alkane signatures from piñon and combined with the δ 13 C values of both piñon and juniper demonstrated that the same trends transcend to the mountainous, grassland to piñon-juniper transition [Wilcox et al, 2003b]. Evidence of legacy grass-C in bare areas has been observed in other southwestern U.S. landscapes following woody encroachment [Boutton et al, 1999;Bai et al, 2012 ].…”
Section: Change In the Source Of C Over Vegetation Transitionsmentioning
confidence: 99%